Identifikasi Sektor Ekonomi Non-Migas Sebagai Sektor Kunci Perekonomian Provinsi Riau Menggunakan Analisis Tabel Input Output - Wan Junita Raflah; Teguh Widodo (Politeknik Negeri Batam, 2016)
this study aims to identify the non- oil and gas economic sectors as key sectors to drive economic growth of Riau Province by analyzing the sectoral contribution in the economy of Riau Province based on its output contribution, intermediate demand, final demand and Gross Value Added This study uses Input Output approach, which is to aggregate Input Output Table of Riau Province 2010 into a 25x25 sector matrix. Results of the study show that the sectoral contribution analysis of Riau Province economy in 2010 based on the output contribution, intermediate demand, final demand and Gross Value Added found that the Riau Province economy is dominated by the Oil and Gas Mining sector. However, Food, Beverages and Tobacco Industry sector, trading sector, Pulp, Paper and printing Industry sector, forestry sector, as well as rubber sector are the key sectors of the Riau Province economy other than Oil and Gas sector.